Self Ligating Brackets-A Comprehensive Review - Gopal, Hasini; Rajaram, Krishnaraj; Kannan, Ravi (Journal of Neonatal Surgery, 2025)
Self-ligating brackets (SLBs) are orthodontic appliances that eliminate the need for elastic or metal ligatures to hold the archwire in place. They use a built-in clip or sliding mechanism, reducing friction and enabling more efficient tooth movement. SLBs offer advantages such as shorter treatment duration, fewer appointments, improved oral hygiene and increased patient comfort. Research suggests that these brackets may reduce overall treatment forces, potentially leading to less discomfort. Despite higher initial costs, their benefits make them a popular choice in modern orthodontics for effective and aesthetic treatment.